Stroke characteristics in sprint kayaking - How does seat order influence sychronization in a K2 crew boat? - Tay, C. S.; Kong, P. W. (Journal of Mechanics in Medicine and Biology, 2020)
The purpose of this study was to investigate the how seat order in a K2 crew boat could influence the performance time and stroke synchronization during high intensity sprint kayaking. Sixteen national team sprint kayakers formed eight K2 crews based on preference. Each crew performed two 200-m segments at high intensity in their preferred order (e.g. Paddler A in front, Paddler B behind), and then the reversed order (i.e. Paddler B in front, Paddler A behind). Video analysis identified stroke synchronization based on a four-position model. Magnitude-based inferences were used for statistical analysis. The preferred seat order was 0.5 ± 1.8 s faster than the reversed seat order but the effect was possibly trivial. As four crews were faster in the reversed seat order, data were also rearranged to compare between the slower and faster trials. The faster trials were 1.5 ± 0.5 s quicker than the slower trials, which was a very likely effect. There was no clear effect of seat order on stroke synchronization between the two paddlers. Since faster timing does not always correspond with the preferred sear order, sprint kayak athletes are recommended to try both possible seat orders in a K2 crew boat rather than relying on preference alone. Keywor